Exploring the ordinary: migration, sexuality and crime, and the progression of the 'Agenda' in Irish women's history, 1850s–1950s. Issue 170 (November 2022) - Farrell, Elaine; McCormick, Leanne; Redmond, Jennifer
Abstract: This article reflects on some developments in women's history based on the 1992 'An agenda for women's history in Ireland, 1500–1900', particularly responding to the section authored by Maria Luddy, incorporating work grounded in the nineteenth century up to the first half of the twentieth. Specifically, it considers developments in Irish women's social history over the past thirty years on the period from the 1850s to 1950s. The focus is on themes of poverty and migration, crime, and sexuality, which were touched on in the 'Agenda' and identified as areas for future research. Analysis on these subjects allows for an insight into lived realities for 'ordinary' women. These are areas which reveal the growth and development of historical research and its impact on public narratives and policy. Taking its cue from the 'Agenda', this article also identifies other fruitful research topics that could be further explored in future scholarship.